Análise do potencial econômico do estoque de carbono em unidades de conservação com manguezal no Ceará - Braga, Magda Marinho (2024)
The climate crisis is one of the most challenging environmental problems ever faced by humanity, requiring studies and strategies aimed at understanding the phenomenon and mitigating its effects. In this sense, the use of legally protected green areas to capture and store atmospheric carbon is an efficient strategy to minimize the adverse effects of global warming, thus contributing to the fight against climate change. This research aims to calculate the amount of carbon stored in mangrove vegetation present in Conservation Units (CUs) in the coastal zone of the state of Ceará and its economic potential in the Carbon Credit Market. To this end, an inventory of the biomass in the Environmental Protection Area (APA) of the Pacoti River was carried out. Then, the carbon stock of this biomass and its equivalent in CO2 per hectare of mangrove were calculated. With this primary data, it was possible to estimate the carbon and CO2 stock present in the other CUs with mangroves in the state of Ceará. Finally, an economic analysis of this stock was performed using the average price of carbon credits (equivalent to 1 t/CO2) traded on the stock exchange. The results indicated that the mangrove vegetation, present in the conservation units of the coastal zone of Ceará, stores 189.888,54 t of carbon and 696.890,94 t of CO2, which are worth more than sixty-eight million reais (R$ 68.600.000,00) on the voluntary market alone. This demonstrates that the mangrove has great potential for storing carbon and a significant pecuniary value, reinforcing its ecological and economic importance, which, if well used, can bring benefits to the conservation and recovery of these important regions.